Average Error: 1.6 → 0
Time: 14.0s
Precision: 64
${e}^{\left(-\pi\right)}$
$\left(\sqrt[3]{{e}^{\left(-\pi\right)}} \cdot \sqrt[3]{{e}^{\left(-\pi\right)}}\right) \cdot \sqrt[3]{{e}^{\left(-\pi\right)}}$
{e}^{\left(-\pi\right)}
\left(\sqrt[3]{{e}^{\left(-\pi\right)}} \cdot \sqrt[3]{{e}^{\left(-\pi\right)}}\right) \cdot \sqrt[3]{{e}^{\left(-\pi\right)}}
double f() {
double r2245729 = exp(1.0);
double r2245730 = atan2(1.0, 0.0);
double r2245731 = -r2245730;
double r2245732 = pow(r2245729, r2245731);
return r2245732;
}


double f() {
double r2245733 = exp(1.0);
double r2245734 = atan2(1.0, 0.0);
double r2245735 = -r2245734;
double r2245736 = pow(r2245733, r2245735);
double r2245737 = cbrt(r2245736);
double r2245738 = r2245737 * r2245737;
double r2245739 = r2245738 * r2245737;
return r2245739;
}



Try it out

Results

 In Out
Enter valid numbers for all inputs

Derivation

1. Initial program 1.6

${e}^{\left(-\pi\right)}$
2. Using strategy rm

$\leadsto \color{blue}{\left(\sqrt[3]{{e}^{\left(-\pi\right)}} \cdot \sqrt[3]{{e}^{\left(-\pi\right)}}\right) \cdot \sqrt[3]{{e}^{\left(-\pi\right)}}}$
4. Final simplification0

$\leadsto \left(\sqrt[3]{{e}^{\left(-\pi\right)}} \cdot \sqrt[3]{{e}^{\left(-\pi\right)}}\right) \cdot \sqrt[3]{{e}^{\left(-\pi\right)}}$

Reproduce

herbie shell --seed 1
(FPCore ()
:name "E ^ -PI"
:precision binary64
(pow E (- PI)))